AVAILABILITY AND UTILISATION OF LIBRARY INFORMATION RESOURCES IN SECCONDARY SCHOOLS BY SPECIAL PATRON - Emasealu, Helen Uzoezi (International Journal of Knowledge Content Development & Technology, 2022)
This study adopted descriptive survey research method. The population of this study comprised of the hearing impaired students in selected government secondary schools in Rivers state. The population of the hearing impaired students in Rivers State is 257. Simple random sampling technique was used to select a sample size of 159. A self-developed instrument titled “Availability and Utilisation of Library Information Resources Questionnaire (AULIRQ)” was utilized for data collection. 153 responses were collated, indicating a 96.2% response rate. The data collected was arranged and analysed using in frequency count, percentages, and mean and standard deviation. Finding reveals that information resources in the libraries understudied were inadequate and under-utilized. Also, it was established that among other barriers, under-funding is a major barrier to making information resources available for the physically challenged. Based on the findings, recommendations were made.